The Evolving Standards for Facial Plastic Photography in the Age of Social Media - Abraham-Aggarwal, Kiran; Wilson IV, John; Yang, Andrew B.; Frodel, John L. (Facial Plastic Surgery, 2025)
Standardized photography is foundational in facial plastic surgery (FPS) for accurate documentation of outcomes. The increased use of smartphones and social media introduces challenges such as variable lighting, filters, and digital manipulation that can distort results.To examine current FPS photography standards and propose updated guidelines that address the influence of digital platforms. We hypothesize that modern adaptations are required to ensure accuracy and patient trust.Perspective on FPS photography standards in the age of social media.We reviewed published recommendations, historical practices, and recent studies on perioperative FPS photography, including the impact of smartphone technology and social media on standardization.Findings highlight that smartphone photography and social media images often introduce bias through inconsistent angles, lighting, and digital enhancements.Revised photographic guidelines that integrate digital-era considerations are necessary to maintain accuracy, transparency, and ethical standards in FPS.
Keywords: photography; guidelines; preoperative photography; clinical outcomes